The deep-pocket effect of internal capital markets - Xavier Boutin; Giacinta Cestone; Chiara Fumagalli; Giovanni Pica; Nicolas Serrano-Velarde (Fondazione Eni Enrico Mattei (FEEM), 2009)
We provide evidence suggesting that incumbents' access to group deep pockets has a negative impact on entry in product markets. Relying on a unique French data set on business groups, our paper presents three major findings. First, the amount of cash holdings owned by incumbent-affiliated groups is negatively related to entry in a market. Second, the impact on entry of group deep pockets is more important in markets where access to external funding is likely to be more difficult. Third, the entry deterring effect of group deep pockets is more pronounced when groups have more active internal capital markets. Our findings suggest that internal capital markets operate within corporate groups and that they have a potential anti-competitive effect.
Keywords: G32; G38; L41; 330; Business Groups; Cash Holdings; Internal Capital Markets; Deep-Pockets; Market Entry